Evaluation of Yield and Nitrogen Use Efficiency in Wheat as Influenced by Nitrogen Level and Variety (Journal of the Bangladesh Agricultural University, 2025)
The efficient management of nitrogen (N) is essential for improving wheat yield and nitrogen use efficiency (NUE), which may differ due to variation in growth duration and nitrogen dynamics in the soil. Therefore, a field experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh, from November 2024 to March 2025 to evaluate the influence of wheat variety by different nitrogen levels on the yield and nitrogen use efficiency. Three wheat varieties, viz. BWMRI Gom-1, BWMRI Gom-2, BWMRI Gom-5 and four levels of nitrogen viz. i) 0 kg N ha-1, ii) 45 kg N ha-1, iii) 90 kg N ha-1, iv) 135 kg N ha-1 were considered as treatments. Nitrogen was applied as per the treatments of the study. The experiment was laid out in a randomized complete block design (RCBD) with three replications. Results revealed that the variety BWMRI Gom-2 produced the highest plant height (88.06 cm), grain yield (2.64 t ha-1), straw yield (3.80 t ha-1), biological yield (6.43 t ha-1), harvest index (40.68%) and nitrogen use efficiency (43.45%). In case of nitrogen level, the highest plant height (90.32 cm), grain yield (3.30 t ha-1), straw yield (4.61 t ha-1), biological yield (7.90 t ha-1), harvest index (41.79%) and nitrogen use efficiency (62.54%) were recorded from the treatment 90 kg N ha-1. The yield-contributing characters and yield of wheat increased with increasing nitrogen levels up to 90 kg N ha-1. Variety and nitrogen levels significantly influenced wheat yield. The results of the present study showed that the highest grain yield (3.44 t ha-1) and nitrogen use efficiency (66.13%) were obtained from the variety BWMRI Gom-2 with an application of 90 kg N ha-1. Grain yield and nitrogen use efficiency were the highest from the interaction between the variety BWMRI Gom-2 and 90 kg N ha-1. Thus, the wheat variety BWMRI Gom-2 can be successfully cultivated with mentioned dose for higher yield and nitrogen use efficiency.J Bangladesh Agril Univ 23(3): 331 – 341, 2025